Photoelectron spectroscopy of a series of acetate and propionate esters. (October 2017) - Śmiałek, Małgorzata A.; Guthmuller, Julien; MacDonald, Michael A.; Zuin, Lucia; Delwiche, Jacques; Hubin-Franskin, Marie-Jeanne; Lesniewski, Tadeusz; Mason, Nigel J.; Limão-Vieira, Paulo
Highlights: Presents the valence shell structure and the PE for acetate and propionate esters. Data obtained through VUV PES and ab initio calculations. The most distinctive vibrational transition is a CO stretch combined with a CO stretch. Ionization energy depends on the size of the molecule, not much on its conformation. Abstract: The electronic state and photoionization spectroscopy of a series of acetate esters: methyl acetate, isopropyl acetate, butyl acetate and pentyl acetate as well as two propionates: methyl propionate and ethyl propionate, have been determined using vacuum-ultraviolet photoelectron spectroscopy. These experimental investigations are complemented by ab initio calculations. The measured first adiabatic and vertical ionization energies were determined as: 10.21 and 10.45 eV for methyl acetate, 9.99 and 10.22 eV for isopropyl acetate, 10.07 and 10.26 eV for butyl acetate, 10.01 and 10.22 eV for pentyl acetate, 10.16 and 10.36 eV for methyl propionate and 9.99 and 10.18 eV for ethyl propionate. For the four smaller esters vibrational transitions were calculated and compared with those identified in the photoelectron spectrum, revealing the most distinctive ones to be a CO stretch combined with a CO stretch. The ionization energies of methyl and ethyl esters as well as for a series of formates and acetates were compared showing a clear dependence of the value of the ionization energy on the size of the molecule with very little influence of its conformation.